Alter-Value in Data Reuse: Non-Designated Communities and Creative Processes. (22nd May 2020) - Boutard, Guillaume
This paper builds on the investigation of data reuse in creative processes to discuss 'epistemic pluralism' and data 'alter-value' in research data management. Focussing on a specific non-designated community, we conducted semi-structured interviews with five artists in relation to five works. Data reuse is a critical component of all these works. The qualitative content analysis brings to light agonistic-antagonistic practices in data reuse and shows multiple deconstructions of the notion of data value as it is portrayed in the data reuse literature. Finally, the paper brings to light the benefits of including such practices in the conceptualization of data curation.